Rodent-borne emerging viral zoonosis. Hemorrhagic fevers and hantavirus infections in South America - Enria, Delia (2000)
Fil: Enria, Delia. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Virales Humanas; Argentina.